Analysis of magnetic fields on a levitating coaxial and non-coaxial aluminum disc - Narukullapati, Bharath Kumar; Bhattacharya, T K; P, Jhansi Lakshmi (International Journal of Engineering and Technology, 2018)
The electromagnetic field calculations for a levitating aluminum disc involve integro-differential equations and the solution of these equations is difficult to obtain using conventional techniques especially when the disc is coaxially away from the axis of the coils. Over the years many analytical, semi-analytical and numerical techniques have been proposed to calculate the magnetic fields on the disc when it is coaxial with the coils. In this paper, a mathematical formulation has been developed to obtain the magnetic fields on a conducting disc using a numerical technique at different positions of the levitation and for different disc discretization’s. The numerical technique developed here is based on Finite Difference Method. Since the magnetic fields on the disc are due to the coil currents and eddy currents in the disc, first a mathematical formulation is done to calculate fields due to exciting coil currents and then a numerical technique is used to calculate fields due to eddy currents on the disc. Also, the magnetic fields on the disc are calculated when the disc moves away from the axis of the coil. A MATLAB program is developed to calculate these fields.